ICRF - volume charge - antenna edge interactions in the torsatrons U-3M and U-2M Part 1. Formation of a volume space charge (VSC) of positive ions - Berezhnyj, V.L. (Вопросы атомной науки и техники, 2016)
A feature of fusion plasma rf discharges is the formation of near-wall volume-space charges (VSC) of positive ions. Nonlinear properties of VSC layers exert a determining influence on the rf discharge characteristics. The rf discharge includes the inductive and capacitive elements of the power input into the plasma, i.e. it is a hybrid discharge.